'MaxClover' grazing experiment: I. Annual yields, botanical composition and growth rates of six dryland pastures over nine years. (18th July 2014) - Mills, A.; Lucas, R. J.; Moot, D. J.
Abstract Six dryland pastures were established at Lincoln University, Canterbury, New Zealand, in February 2002. Production and persistence of cocksfoot pastures established with subterranean, balansa, white or Caucasian clovers, and a perennial ryegrass‐white clover control and a lucerne monoculture were monitored for nine years. Total annual dry‐matter (10.0–18·5 t DM ha−1) and sown legume yields from the lucerne monoculture exceeded those from the grass‐based pastures in all but one year. The lowest lucerne yield (10 t ha−1 yr−1) occurred in Year 4, when spring snow caused ungrazed lucerne to lodge and senesce. Cocksfoot with subterranean clover was the most productive grass‐based pasture. Yields were 8·7–13·0 t DM ha−1 annually. Subterranean clover yields were 2·4–3·7 t ha−1 in six of the nine years which represented 26–32% of total annual production. In all cocksfoot‐based pastures, the contribution of sown pasture components decreased at a rate equivalent to 3·3 ± 0·05% per year (R2 = 0·83) and sown components accounted for 65% of total yield in Year 9. In contrast, sown components represented only 13% of total yield in the ryegrass‐white clover pastures in Year 9, and their contribution declined at 10·1 ± 0·9% per year (R2 = 0·94). By Year 9, 79% of the 6.6 t ha−1 produced from the ryegrass‐white clover pasture was from unsown species and 7% was dead material. For maximum production and persistence, dryland farmers on 450–780 mm yr−1 rainfall should grow lucerne or cocksfoot‐subterranean clover pastures in preference to ryegrass and white clover. Inclusion of white clover as a secondary legume component to sub clover would offer opportunities to respond to unpredictable summer rainfall after sub clover has set seed.